Basic competencies of the graduates of BRAC's non-formal schools: levels and trends from 1995 to 1999 - Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2020)
Based on the Declaration of the World Conference on Education held in Jomtien in 1990, BRAC designed an instrument to measure the level of basic education of Bangladeshi children. The Research and Evaluation Division of BRAC regularly monitors the performance of the graduates of BRAC's non-formal schools through this instrument. This report presents the basic educational status of the graduates of three cohorts of 1995, 1997 and 1999. Three independent samples were drawn from three cohorts and the learners were tested after nine/ten months of their graduation. The sample from 1995 cohort was also tested in 1997 and 1999; and the sample from 1997 cohort was tested in 1999. Children from three systems of BRAC schools were assessed: those in Non Formal Primary Education (NFPE) and in Basic Education for Older Children (BEOC) which was directly operated by BRAC, and NFPE under the Education Support Programme (ESP) which are operated by other NGOs with support from BRAC. The sample sizes for the three independent surveys were 1259 each. Among the 1,259 graduates of 1995 and 1997 each, 812 of 1995 and 991 of 1997 could be traced in 1999; these are respectively 64.5% and 78.7% of the original samples. Of the sample of 1995 graduates only 54.3% were common in all the three surveys.